2015
DOI: 10.1109/access.2015.2508789
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Spatial Distribution Identification of Base Stations in Cellular Networks

Abstract: The performance of cellular system significantly depends on its network topology, where the spatial deployment of base stations (BSs) plays a key role in the downlink scenario. Moreover, cellular networks are undergoing a heterogeneous evolution, which introduces unplanned deployment of smaller BSs, thus complicating the performance evaluation even further. In this paper, based on large amount of real BS locations data, we present a comprehensive analysis on the spatial modeling of cellular network structure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 26 publications
1
38
0
Order By: Relevance
“…The closest work to this paper is [3], in which authors have evaluated how much the α-Stable distribution matches the real one in three Chinese cities. In contrast to them, in this work we move five significant steps further by:…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…The closest work to this paper is [3], in which authors have evaluated how much the α-Stable distribution matches the real one in three Chinese cities. In contrast to them, in this work we move five significant steps further by:…”
Section: Introductionmentioning
confidence: 96%
“…• investigating what is the best distribution across different BS deployment scenarios, and not only urban ones like in [3]. Our goal is in fact to find, behind the evidences of α-Stable distribution, also its boundaries, i.e., the limits of applicability of this model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to (22), we can infer that if the BS density in each tier is set properly, maximum EE under the ASE constraint will be achieved. But, it is difficult to solve the optimization problem analytically, because the closed-form expressions of ASE and EE are not easily obtained.…”
Section: Area Spectral Efficiency and Energy Efficiency Tradeoffmentioning
confidence: 99%
“…References [18][19][20][21][22] summarized and compared many kinds of point processes and concluded that Poisson point process (PPP) is the most popular, most tractable, and most important one because of its independence property. Therefore, taking advantage of the PPP, we adopt the stochastic geometry theory to analyze the EE in an ultradense HetNet.…”
Section: Introductionmentioning
confidence: 99%